Fostering 21st-Century Skills for Sustainable Education through Language Learning Beliefs and Practices: A Narrative Inquiry - Rahmawati, Fithriyah; Putikadyanto, Agus Purnomo Ahmad; Efendi, Agik Nur (Entita: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2025)
Moving further to the 21st century, education needs to provide students with essential knowledge and the abilities required for succeeding in a global interconnection and sustainable environment. The role of foreign language education is crucial in this transformation, but the perceptions of teachers and students regarding language learning are just as significant. Through narrative inquiry, this study explored the foreign language teachers' beliefs toward language learning and a story of how the beliefs foster 21st-century skills- like critical thinking, communication, and global awareness- within a sustainable education context. The analysis revealed two topics of discussion: 1) the influence of personal beliefs on teaching practices and 2) the emphasis on 21st-century skills in classroom practice for sustainable education. The study provides implications for teachers, practitioners, educational institutions, and stakeholders.